North American lower-extremity revascularization and amputation during COVID-19: Observations from the Vascular Quality Initiative. (December 2021) - Lou, Jun-Yang; Kennedy, Kevin F; Menard, Matthew T; Abbott, J Dawn; Secemsky, Eric A; Goodney, Philip P; Saad, Marwan; Soukas, Peter A; Hyder, Omar N; Aronow, Herbert D
Introduction: The coronavirus disease 2019 (COVID-19) pandemic's impact on vascular procedural volumes and outcomes has not been fully characterized. Methods: Volume and outcome data before (1/2019 – 2/2020), during (3/2020 – 4/2020), and following (5/2020 – 6/2020) the initial pandemic surge were obtained from the Vascular Quality Initiative (VQI). Volume changes were determined using interrupted Poisson time series regression. Adjusted mortality was estimated using multivariable logistic regression. Results: The final cohort comprised 57, 181 patients from 147 US and Canadian sites. Overall procedure volumes fell 35.2% (95% CI 31.9%, 38.4%, p < 0.001) during and 19.8% (95% CI 16.8%, 22.9%, p < 0.001) following the surge, compared with presurge months. Procedure volumes fell 71.1% for claudication (95% CI 55.6%, 86.4%, p < 0.001) and 15.9% for chronic limb-threatening ischemia (CLTI) (95% CI 11.9%, 19.8%, p < 0.001) but remained unchanged for acute limb ischemia (ALI) when comparing surge to presurge months. Adjusted mortality was significantly higher among those with claudication (0.5% vs 0.1%; OR 4.38 [95% CI 1.42, 13.5], p = 0.01) and ALI (6.4% vs 4.4%; OR 2.63 [95% CI 1.39, 4.98], p = 0.003) when comparing postsurge with presurge periods. Conclusion: The first North American COVID-19 pandemic surge was associated with a significant and sustained decline in both elective and nonelective lower-extremity vascular procedural volumes. When compared with presurge patients, in-hospital mortality increased for those with claudication and ALI following the surge.